Hubungan antara Profilaksis Kotrimoksazol dan Prevalensi Toksoplasmosis pada Pasien HIV Positif di Jember (The Association Between Prophylactic Cotrimoxazole and the Prevalence Toxoplasmosis in HIV-Positive Patients in Jember) - Elly Febry Taufany; Afifah Machlaurin; Prihwanto Budi Subagijo (UPT Percetakan dan Penerbitan Universitas Jember, 2018)
Human immunodeficiency virus (HIV) is a virus that causes acquired immune deficiency syndrome (AIDS). HIV is a high mortality disease and the number of patients is increasing recent days. Based on dr. Soebandi Jember Hospital report in 2015, there were 1,492 HIV patients and 455 people received antiretroviral (ARV) therapy. Toxoplasmosis is one of opportunistic infections commonly found in HIV patients in central nervous system. WHO has issued guidelines for the use of cotrimoxazole as prophylaxis in HIV positive people. The purpose of this study was to determine the relationship between cotrimoxazole prophylaxis and the incidence of toxoplasmosis. This research was a case control study with retrospective approach and used chi-square analysis. The results showed that most patients were male (57%), 20-29 years in age (50%), and 41-60 kg in weight (64%). Based on the CD4 level, most HIV patients were less than 350/mm3 (96%) and total lymphocite count (TLC) also less than 1,200/mm3 (42%). There were 1 patient from 76 patients with cotrimoxazole prophylaxis and 7 patients from 52 patient without cotrimoxazole prophylaxis who developed toxoplasmosis. Based on chi-square analysis, cotrimoxazole prophylaxis reduce the incidence of toxoplasmosis in HIV positive (p-value 0,004). Keywords: HIV/AIDS, prophilaxis therapy of cotrimoxazole, toxoplasmosis infection